Development of a Health Screening Package Under the Universal Health Coverage: The Role of Health Technology Assessment - Teerawattananon, Yot (Health Econ, 2016)
This study reports the systematic development of a population‐based health screening package for all Thai people under the universal health coverage (UHC). To determine major disease areas and health problems for which health screening could mitigate health burden, a consultation process was conducted in a systematic, participatory, and evidence‐based manner that involved 41 stakeholders in a half‐day workshop. Twelve diseases/health problems were identified during the discussion. Subsequently, health technology assessments, including systematic review and meta‐analysis of health benefits as well as economic evaluations and budget impact analyses of corresponding population‐based screening interventions, were completed. The results led to advice against elements of current clinical practice, such as annual chest X‐rays and particular blood tests (e.g. kidney function test), and indicated that the introduction of certain new population‐based health screening programs, such as for chronic hepatitis B, would provide substantial health and economic benefits to the Thais. The final results were presented to a wide group of stakeholders, including decision‐makers at the Ministry of Public Health and the public health insurance schemes, to verify and validate the findings and policy recommendations. The package has been endorsed by the Thai UHC Benefit Package Committee for implementation in fiscal year 2016. © 2016 The Authors. Health Economics published by John Wiley & Sons Ltd.